Price and Variance Transmission from the U.S. Capital Market to Foreign Capital Markets; Evidence in the Financial Times Actuaries World Indices from 1991 to 1993 - Parisi, Franco (Estudios de Administración, 1995)
The U.S. impact on the Financial Times Actuaries World Indices (FTAWIS) is significant, in both pricing and variance. The pricing effect from the U.S. to the FTAWIS is significant in all cases. The U.S. spillover effect is significant in 18 cases over a total of 22 countries considered in the sample. This leads to the conclusion that the FTAWIS incorporate the information generated in the U.S. capital market in both pricing and variance.